أسباب تلف أحجار البناء في المباني الأثرية القديمة وبعض طرق الترميم - طارق أصلان; بسام حويجة; حمزة نظام (Tishreen University, 2019)
تتعرض المنشآت الأثرية كغيرها من المنشآت المدنية للاهتراء والتلف بتأثير عوامل مختلفة، إلا أن ترميم وإعادة تأهيل هذه المنشآت له مبادئ خاصة ناتجة عن خصوصية هذه المنشآت ، سواء من حيث أسلوب الإنشاء والمواد المستخدمة أو من حيث القيمة الأثرية ، والتي تفرض على العاملين في مجال الترميم الالتزام بجملةٍ من المبادئ نابعة من احترام الأصالة التاريخية للمنشأ. ويعرض هذا البحث أسباب تلف أحجار البناء في المباني الأثرية القديمة، كما يعرض منهجا لتقييم هذا التلف ومواد المعالجة الحديثة ومعايير المعالجة الناجحة. Historic buildings, as other civil structures, face decay and corrosion, caused by several factors. the restoration and restructure of historic buildings have certain principles derived from their particularity; concerning the structural style the materials involved, or their heritage value imposing on the workers of their field the commitment to a set of principles emerged from the respect to the historic authenticity of the buildings. This study discusses the reasons of stone decay in the historic building, methodology to assess this decay, the recent materials used for treatment and the criteria of successful treatment